2013
DOI: 10.1111/j.1365-2125.2012.04426.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preconceptional paternal drug exposure on birth outcomes: cohort study of 340 000 pregnancies using Norwegian population‐based databases

Abstract: AIMSWe aimed to explore associations between drugs dispensed to the father prior to conception and pregnancy outcomes, such as pre-term birth, perinatal mortality, foetal growth retardation and birth defects. METHODSIn this cohort study, two population-based registries, the Medical Birth Registry of Norway and the Norwegian Prescription Database, were linked. The study cohort consisted of 340 000 pregnancies in 2004-10. The association between specific drugs dispensed to the fathers during the last 3 months pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
(32 reference statements)
2
22
0
2
Order By: Relevance
“…A previous study of SCS use by men in Norway (based on 1477 prednisolone‐exposed fathers) suggested an OR of any birth defect of 1.2 (95% CI: 0.9–1.5) . Although this study is reassuring, our current study was over a longer period of time, had distinct categories of corticosteroid ‘users’ and had a larger number of fathers who filled prescriptions for corticosteroids prior to conception.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…A previous study of SCS use by men in Norway (based on 1477 prednisolone‐exposed fathers) suggested an OR of any birth defect of 1.2 (95% CI: 0.9–1.5) . Although this study is reassuring, our current study was over a longer period of time, had distinct categories of corticosteroid ‘users’ and had a larger number of fathers who filled prescriptions for corticosteroids prior to conception.…”
Section: Discussionsupporting
confidence: 43%
“…Types of CAs according to ICD-10 SCS exposed (current users 1 + Current users 2) Number (%) 1 1 Children with CAs might have more than one type of congenital abnormality. 2 No distinct pattern of CAs within this group. 3 Excluding Q5.59 undescended testis.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Os mecanismos envolvidos podem ser por ações mutagênicas diretas, distúrbios na espermatogênese ou a transferência de metabólitos ativos para a mãe por meio do sêmen. Apesar de haver inconsistência de alguns achados, estudos epidemiológicos sugerem a associação entre o uso de diazepan pelo pai e o risco aumentado de mortalidade perinatal e retardo de crescimento intrauterino (40,41). Ainda sobre as alterações com a espermatogênese estudos apontam o uso da finasterida como risco para anomalias congênitas (42) Exposição aos medicamentos de risco.…”
Section: Rompimento Das Células Da Crista Neuralunclassified